The follow-up study on patients of Amyotrophic lateral sclerosis - Song Bong-kuen; Park Man-yong; Lim Na-ra; Kim Sung-ha; Kim Sung-chul (Korean Pharmacopuncture Institute, 2010)
Objectives : This study was to investigate the effects of Oriental medical treatment on ALS. Methods : We investigated 12 ALS patients which were admitted to Gwang-Ju O.M.hospital for 3 months and follow-up at 8 months after discharge. All patients were treated by SAAM-acupuncture, herb medication, Bee venom Pharmacopuncture therapy, Needle-embedding therapy, etc and after discharge self-therapy at home. We evaluated patients using the Amyotrophic lateral sclerosis Functional Rating Scale-Revised(ALSFRS-R), Medical Research Council (MRC) Scale. Results : After 1 month, mean ALSFRS-R score of patients was 29.08±7.99, 2 months 28.70±7.17, 3months 28.16±8.23, 1 year 21.33±9.93 and mean MRC Scale of patients was 25.34±8.45, 2 months 25.34±8.45, 3months 21.56±9.20. But in both cases, the variation was not statistically significant. Conclusions : We think that the results of this case be a pilot study that proves the effect of Oriental Medical treatment on ALS.